Polymorphisms of human placental alkaline phosphatase are associated with in vitro fertilization success and recurrent pregnancy loss (2014)
Fertility is a quantitative, complex character governed by a considerable number of genes. Despite clinical and scientific advances, several cases of human infertility remain unexplained. In the present study, using a positional cloning approach in a mouse model of interspecific recombinant lines, a candidate gene, ALPP, encoding the placental alkaline phosphatase, was identified as being potentially involved in recurrent spontaneous abortion. We then analyzed patients for detecting putative associations between ALPP polymorphisms, in vitro fertilization failures, and miscarriages. ALPP was sequenced in 100 controls and 100 patients affected by recurrent spontaneous abortion, from the same ethnic background. The frequency of several alleles and allelic combinations were different between recurrent spontaneous abortion and control women. One polymorphism induced a coding substitution (Ile89Leu) that was associated with a decreased risk of abortion and in vitro fertilization failure. Thereafter, the population was increased by the analysis of 92 additional controls and 612 additional patients for the coding polymorphism Ile89Leu. We finally show, by functional analysis, that the 89Leu placental alkaline phosphatase has an enhanced alkaline phosphatase activity. This study suggests that ALPP genotyping could be a strong predictor of implantation success. © 2014 American Society for Investigative Pathology.